2022
DOI: 10.18805/bkap397
|View full text |Cite
|
Sign up to set email alerts
|

Outlier Removal in Sheep Farm Datasets Using Winsorization

Abstract: Background: Sheep farm data is often biased by extreme values which are generally introduced due to errors in manual measurement. These values interfere with the accuracy of estimations especially in state-of-the-art techniques like Machine Learning. Methods: Therefore, winsorization technique was attempted for the removal of outliers from sheep farm data data for 11 years (2011-2021) for body weights at different ages. Some outliers were deliberately introduced into the data to check the efficiency of the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…the upper and lower 10% of data to the 90th percentile with a little introduction of error. Hamadani et al 17 also reported similar results while using the winsorization technique. A two-sided winsorization approach was used in this study which was also reported to be better than the one-sided approach by Chambers et al 18 .…”
Section: Discussionmentioning
confidence: 65%
“…the upper and lower 10% of data to the 90th percentile with a little introduction of error. Hamadani et al 17 also reported similar results while using the winsorization technique. A two-sided winsorization approach was used in this study which was also reported to be better than the one-sided approach by Chambers et al 18 .…”
Section: Discussionmentioning
confidence: 65%
“…the upper and lower 10% of data to the 90th percentile with a little introduction of error. A two-sided winsorization approach was used in this study which was also reported to be better than the one-sided approach by Chambers et al 28 and Hamadani et al 29 .…”
Section: Discussionmentioning
confidence: 80%